Geographical information system (GIS) applied to fisheries data: The case of Italian demersal resources - Corsi F.; Agnesi S.; Schintu P.; Ardizzone G. (Dynamique des populations marines, 1998)
A project funded by the European Commission to produce charts for the distribution of demersal fish resources has been the occasion to implement the first nucleus of a GIS (Geographical Information System) of the fisheries resources in the Italian seas. The aim of the system is to structure and manage both geographic and alphanumeric data to allow a high degree of diversification in the analyses. This paper presents the process of implementation of the centralized system together with the basic interpolation analyses used to produce the charts of the distribution of ten target species.
Deuxième Réunion du Groupe de Travail DYNPOP, 1996/10/02-05, Genova (Italy)